The association between social media use and well-being during quarantine period: testing a moderated mediation model - Zhu, Leling; Xiao, Shuaijie; Yan, Xinyu; Zhou, Shuijia; Yang, Jiemin; Yuan, Jiajin (Frontiers in Psychology, 2023)
Objectives Social media use (SMU) increased dramatically during COVID-19 due to policies such as long-term quarantine. Given that SMU has complex effects on individuals’ well-being, this study aimed to explore the relationship between SMU and subjective well-being and the influencing factors in the context of the pandemic in China. Methods A total of 895 adults (413 males) in different risk areas across China participated in this study. They provided self-reported data on subjective well-being, social media use, adaptive humor, and other demographic variables. Results It revealed that SMU was positively associated with individual well-being, an effect partially mediated by the score of adaptive humor. Furthermore, the effect of SMU on adaptive humor was moderated by trait optimism, with the effect more robust in high (vs. low) optimistic individuals. Conclusion This study explored the positive effects of SMU on individuals’ well-being, suggesting that individuals may better cope with negative experiences and maintain well-being under quarantine by showing more adaptive humor on social media.